Nonlinear impedance of a microwave-driven Josephson junction with noise - COFFEY, WILLIAM THOMAS; KALYMYKOV, YURI PETROVICH (American Physical Society, 2000)
The nonlinear impedance of a point Josephson junction is calculated under various conditions for the resistively shunted junction model in the presence of noise. The calculation proceeds by solving the Langevin equation for the mechanical problem of a Brownian particle in a tilted cosine potential in the presence of a strong ac force ignoring inertial effects. The exact solution of the infinite hierarchy of equations for the moments ~expectation values of the Fourier components of the phase angle!, which describe the dynamics of the junction, is expressed in terms of a matrix continued fraction. This solution allows one to evaluate the nonlinear response of the junction ~nonlinear microwave impedance, for example! to an ac microwave current of arbitrary amplitude. Strong nonlinear effects in the resistance and the reactance are observed for large ac currents as is demonstrated by plotting the nonlinear response characteristics as a function of the model parameters. For weak ac currents and low noise strengths, our results agree closely with previously available linear response and nonlinear response noiseless solutions, respectively. Applications of the model to the interpretation of recent experimental data found in the literature for the nonlinear behavior of microwave impedance of superconducting weak links are discussed.
PUBLISHED
Keywords: Electronic & Electrical Engineering